efectuați:b)(x-1)(x+4)-(x-2)(×+2)
c)9(×+1)(×-1)-(3×+1)²
Răspunsuri la întrebare
Răspuns de
1
Salut!:)
b) ( x - 1 ) ( x + 4 ) - ( x - 2 ) ( x + 2 )
( x - 1 ) ( x + 4 ) = x² + 4x - x - 4 = x² + 3x - 4
( x - 2 ) ( x + 2 ) = x² - 4
x² + 3x - 4 - x² + 4 = 3x
c) 9 ( x + 1 ) ( x - 1 ) - ( 3x + 1 ) ²
( x + 1 ) ( x - 1 ) = x² - 1
(3x + 1 ) ² = 9x² + 1 + 6x
9 ( x² - 1 ) - ( 9x² + 1 + 6x )
9x² - 9 - 9x² - 1 - 6x
-10 - 6x
Bafta!:)
marya94:
Mulțumesc frumos
Alte întrebări interesante
Franceza,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă